Adjunctive psychosocial intervention following Hospital discharge for Patients with bipolar disorder and comorbid substance use: A pilot randomized controlled trial. Issue 3 (30th August 2015) - Wenze, Susan J.; Gaudiano, Brandon A.; Weinstock, Lauren M.; Tezanos, Katherine M.; Miller, Ivan W.
Abstract: Bipolar disorder and substance use disorders are highly debilitating conditions, and especially when co-occurring, are associated with a variety of negative outcomes. Surprisingly, there is a relative lack of research on feasible and effective psychosocial treatments for individuals with comorbid bipolar and substance use disorder (BD-SUD), and a dearth of literature examining interventions designed specifically to improve outcomes such as symptoms, functioning, and treatment engagement/adherence following psychiatric hospitalization in this population. In the current paper, we report results of a pilot randomized controlled trial (n=30), comparing the recently developed Integrated Treatment Adherence Program, which includes individual and telephone sessions provided to patients and their significant others, versus Enhanced Assessment and Monitoring for those with BD-SUD. Participants who received the Integrated Treatment Adherence Program demonstrated significantly faster and greater improvements in depression, mania, functioning, and values-consistent living than participants randomized to Enhanced Assessment and Monitoring, and there was a trend for increased treatment adherence over time. Results are discussed in light of existing literature and study limitations, and suggestions for future research are proposed. Highlights: We evaluated the Integrated Treatment Adherence Program in a pilot RCT. The Integrated Treatment Adherence Program is an adjunctive psychosocial intervention for bipolar disorder and substance use. The Integrated Treatment Adherence Program includes individual and telephone sessions for patients and significant others. The Integrated Treatment Adherence Program improves depression, mania, functioning, and value-consistent living. The Integrated Treatment Adherence Program is useful for improving outcomes during the post-hospitalization period.